Peer effects in the valuation and practices of food safety: Findings from the study of dairy consumers in India - Chandra, Raj; Munasib, Abdul; Roy, Devesh; Sonkar, Vinay Kumar (Emerald Publishing Limited, 2021)
Information is often available to consumers through their social networks. Focusing on dairy consumers in India, this paper aims to present evidence of peer effects in consumers’ attitudes towards various food safety attributes and food safety practices.Unobserved individual heterogeneities are crucial confounders in the identification of social (endogenous) effects. The identification is based on exploiting within-consumer variation across different aspects of attitude (or practices) related to food safety.This paper uses a novel identification strategy that allows for average effects across attributes and practices to be estimated. Using the strategy, though this paper cannot estimate endogenous effects in each attribute or practice, this paper is able to identify such effects averaged over attributes or practices.Cross-sectional study, caste affiliation is not defined at the right level of granularity.The results suggest that information campaigns aimed at creating awareness about food safety can have social multiplier effects, and this also translates into changes in the practices followed to mitigate food safety risks.In health-related awareness and practices, there are well-established cases of multiplier effects. The most significant example of this is the Pulse Polio campaign in India, where an awareness drives through social multiplier effects had such a significant impact that in 2012 India was declared polio-free. Perhaps, a similar campaign in matters related to food safety could be very fruitful.The methodology and the issue are unique. Little exists in assessing social networks in the context of food safety.